Analysis of Cadre Compliance Levels in Running Health Protocol in the Era of Pandemic Covid-19 in Puskesmas Limo Depok - Sri Wahyuningsih; Hany Yusmaini; Erna Harfiani; Meiskha Bahar (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Covid-19 outbreak that originated in Wuhan's city is spreading very quickly and is currently a pandemic worldwide. Transmission through droplets that come out of the patient's nose or mouth, whether symptomatic or asymptomatic.  Efforts to prevent and fight COVID-19 must be carried out jointly with the community's cooperation and require strong discipline by washing hands frequently, maintaining distance, wearing masks, staying at home, and increasing body power. The purpose of this study was to determine the level of cadre compliance  in carrying out health protocols in the era of the Covid-19 pandemic. This research method with a cross-sectional approach. The respondents were cadres of Limo Health Center, Depok. It was total sampling. The research instrument used a questionnaire of Google Form and analyzed using Chi-Square. The results showed that most of the respondents were included in the 46-60 year interval (51.4%) were highly educated, tertiary education (70%), knowledgeable (54.3%), unemployed (87.1), obeyed the protocol. Health (50%). Compliance increases in the elderly, higher education, sufficient knowledge, work status. conclusion there is no relationship between age (p = 0.632), education level (p = 0.794), knowledge level (p = 0.253), work status (p = 0.074) and compliance with the Covid-19 health protocol.